HIV-1 viral infectivity factor interacts with microtubule-associated protein light chain 3 and inhibits autophagy. (28th January 2015) - Borel, Sophie; Robert-Hebmann, Véronique; Alfaisal, Jamal; Jain, Ashish; Faure, Mathias; Espert, Lucile; Chaloin, Laurent; Paillart, Jean-Christophe; Johansen, Terje; Biard-Piechaczyk, Martine
<x xml:space="preserve">Abstract</x> Objective: Autophagy, an important antiviral process triggered during HIV-1 entry by gp41-dependent membrane fusion, is repressed in infected CD4+ T cells by an unknown mechanism. The aim of this study was to identify the role of viral infectivity factor (Vif) in the autophagy blockade. Design/methods: To determine the role of Vif in autophagy inhibition, we used cell lines that express CD4 and CXCR4 and primary CD4+ T cells. Pull-down experiments, immunoprecipitation assays and computational analyses were performed to analyze the interaction between Vif and microtubule-associated protein light chain 3B (LC3B), a major autophagy component, in presence or absence of the antiviral host factor apolipoprotein B mRNA-editing enzyme-catalytic polypeptide-like 3G (APOBEC3G), after HIV-1 infection or ectopic expression of Vif. Autophagy was analyzed after infection by viruses expressing Vif (NL4.3) or not (NL4.3ΔVif), or after exogenous Vif expression. Results: We demonstrate that the C-terminal part of Vif interacts directly with LC3B, independently of the presence of APOBEC3G.Vif binds to pro-LC3 and autophagy-related protein 4-cleaved LC3 forms, and glycine 120, the amino acid conjugated to phosphatidylethanolamine on autophagosomes, is required. Importantly, we evidence that Vif inhibits autophagy during HIV-1 infection. Indeed, autophagy is detected in target cells infected by NL4.3ΔVif, but prevented in cells infected by NL4.3. Furthermore, autophagy triggered in NL4.3ΔVif-infected cells is inhibited when Vif is expressed in trans but is still active when target cells express a mutant of Vif that binds weakly to LC3B. Conclusion: Our study unveils that Vif inhibits autophagy independently of its action on APOBEC3G and, therefore, suggest a new function of this viral protein in restricting innate antiviral mechanisms.